Znaczenie przywództwa w procesie zarządzania organizacjami o strukturach zhierarchizowanych: The importance of leadership in the management of organizations with hierarchical structures - Wyrębek, Henryk (Management and Administration Journal, 2021)
Leadership in organizations is one of the most important issues discussed in the contemporary literature. The concept of leadership and the phenomenon of this phenomenon still appear to be insufficiently described. At the same time leadership is one of the most important elements for success of the organization. Efficient leaders often able to prepare the organization for the next challenges of the environment. Lack of leadership in certain situations or inappropriate leadership may in the short term lead to a well-functioning organization crisis. Understanding what the leadership is extremely important for the organization. This article has been hypothesized that such features are the leaders that are particularly beneficial in the management of organizations with hierarchical structures and those that are in the process less important.